Power Doppler sonographic pattern of acute pyelonephritis in children: comparison with CT - Dacher, JN; Pfister, C; Monroc, M; Eurin, D; LeDosseur, P (American journal of roentgenology (1976), 1996)
Focal areas of decreased perfusion may be shown by power Doppler sonography in children with acute pyelonephritis. The purposes of this study were to assess the ability of power Doppler sonography to reveal acute pyelonephritis and to compare the sonographic images with enhanced CT images. We performed B-mode sonography, power Doppler sonography, and enhanced CT (reference method) of the kidneys of 30 children with symptoms suggesting upper urinary tract infection. All imaging studies were obtained within 24 hr of admission of each child to our hospital. Power Doppler sonography was performed with the same equipment and the same settings for all children. Imaging studies were performed before the results of urine cultures were obtained. Triangular areas of decreased perfusion visible on both longitudinal and axial scans were considered indicative of acute pyelonephritis on power Doppler sonographic images. On CT images, areas of decreased attenuation of the renal parenchyma visible immediately after IV injection of iodinated contrast agent or areas of increased attenuation on delayed scans were considered indicative of acute pyelonephritis. Power Doppler sonography and CT were compared for each renal pole (n = 120). For 17 (89%) of the 19 patients with CT-proven acute pyelonephritis, power Doppler sonography diagnosed this condition on the correct side. Seventeen (77%) of the 22 poles showing acute pyelonephritis on CT scans were also revealed by power Doppler sonography. The two patients in whom acute pyelonephritis was not revealed by power Doppler sonography were an obese 15-year-old girl and a 7-year-old boy with right upper pole pyelonephritis. This boy was one of the first patients to be included in the study. Also, in an obese 11-year-old girl, a false-positive indication of pyelonephritis was given by power Doppler sonography. Power Doppler sonography seems to be significantly more sensitive than conventional sonography for the detection of acute pyelonephritis in children. This noninvasive technique should be able to replace CT or dimercaptosuccinic acid scintigraphy in many children with urinary tract infections.